Linear viscous approach to predict rut depth in asphalt mixtures - Al-Mosawe, Hasan; Thom, Nicholas; Airey, Gordon; Albayati, Amjad (Elsevier, 2018)
Rutting in asphalt mixtures is a very common type of distress. It occurs due to the heavy load applied and slow movement of traffic. Rutting needs to be predicted to avoid major deformation to the pavement. A simple linear viscous method is used in this paper to predict the rutting in asphalt mixtures by using a multi-layer linear computer programme (BISAR). The material properties were derived from the Repeated Load Axial Test (RLAT) and represented by a strain-dependent axial viscosity. The axial viscosity was used in an incremental multi-layer linear viscous analysis to calculate the deformation rate during each increment, and therefore the overall development of rutting. The method has been applied for six mixtures and at different temperatures. Finally, field data has also been used to check the applicability of the approach in real pavement design.